(untitled) (Eurasian Journal of Philology Science and Education, 2025)
Phraseological units have great meaningful power and potential of form. In this regard, the study of phraseological expressions as an original statement created based on ethnocultural heritage, national code, national cognition is of great importance. And the features and methods of analyzing the problem of translating the rich phraseological fund of the native language into another language are systematically comprehensively considered, and its nature has not yet been disclosed. Many studies and dictionaries concerning the translation of the Kazakh language into Russian and related Turkish languages, the absence of systematically compiled phraseological dictionaries before this period, indicates the relevance of the research topic. Collecting, fully mastering and passing on to the next generation our vocabulary, which has survived to this day in the memory of such a people, is one of the main tasks that has developed in any field of science today. The article contains a well-known concept called the “Sepir-Worf hypothesis”, the definition of which is given. There is also information about the origin of the term" intercultural communication". Phraseological units clearly reflect the specifics of National thinking, mentality, attitude and worldview of representatives of the language. It is also important to translate them into another language. The article explains the meaning of phraseological units found in M. Auezov’s epic “The Path of Abai” and considers the features of their translation into Russian, Turkish and Kyrgyz in the article with specific examples. The translation of M. Auezov’s epic “The Path of Abai” is completedby translators A. Nikolskaya, T. Nurtazin and L. Sobolev, A. Kim and others. The purpose of the article is determined by the relevance of the role and importance of translation in intercultural communication. As a result, the recommendations were given on the transmission of phraseological units of an ethnolinguistic nature. Key words: phraseological unit, literary translation, intercultural communication.